A comparative analysis of the study of hadith science in the hadith schools of Mawarounnahr and al-Azhar - Kholmurotov Asadulla Eshmamatovich (Zien Journals, 2021)
In the study of hadith sciences, a comparative analysis of the methods of the two schools of hadith schools, namely Movarounnahr and al-Azhar, was made. In the process of analysis, evidence was presented on the basis of historical and scientific sources. The differences and interrelationships between schools on these methods were also highlighted
Keywords: Hadith; Sunnah; education; prayer; Qur'an